High-density electromyography biofeedback during robotic wrist exercises for reducing co-activation of antagonist muscles: a case report. Issue 1 (30th December 2020) - Cikajlo, Imre; Zadravec, Matjaž; Matjačič, Zlatko; Urh, Filip; Šavc, Martin; Kranjec, Jernej; Divjak, Matjaž; Frančič, Aljaž; Potočnik, Božidar; Holobar, Aleš
Abstract : High-density (HD) electrodes have been introduced in research and diagnostic electromyography. Recent advances in technology offer an opportunity for using the HDEMG signal as biofeedback in stroke rehabilitation. The purpose of this case study was to test the feasibility of using two 5 × 13 electrode arrays for providing real-time HDEMG biofeedback and the preliminary outcome of combining HDEMG biofeedback with robotic wrist exercises over 4 weeks in a person who suffered a stroke 26 months earlier. The isometric wrist flexion/extension task required to keep the paretic agonist activity within variable preset limits with minimal activation of the antagonists. The participant was able to utilize the provided biofeedback interface and after eight sessions significantly decreased co-activation in the antagonist wrist extensor muscles during isometric wrist flexion. The HDEMG biofeedback seems feasible and may be used alone or in combination with robotic therapy for increasing the selectivity of muscle activation after stroke.